Addition and cycloaddition reactions of Phosphinyl- and Phosphonyl-2H-Azirines, Nitrosoalkenes and Azoalkenes - Lemos, A. (2009)
An overview of the use of 2H-azirines, conjugated nitrosoalkenes and conjugated azoalkenes bearing phosphorus substituents in addition and cycloaddition reactions is presented, focused on strategies for the synthesis of aminophosphonate and aminophosphine oxide derivatives.